НАУЧНЫЕ ОСНОВЫ ИЗУЧЕНИЯ ХИМИЧЕСКОГО СОСТАВА КРУП НА НОВОЙ ТЕХНОЛОГИИ - Рахматов Элдор Райхонович (Journal of new century innovations, 2024)
Abstract. Scientific justification of possibility of enrichment of food by proteins, vitamins, mineral substances, flavonoids and other biologically active agents containing in secondary raw materials of groats production is presented in article.